Plan de marketing para la organización Aprocuy, productora y comercializadora de cuyes en el cantón Cayambe - Naranjo Caiza, Evelyn Fernanda (2015)
Guinea pig growing in Ecuador is an activity that has been rising through years since rural communities, especially in the high lands, because the people have made this activity their economy. Even if it has been developed as a familiar activity, some people have developed certain technic for the production process to obtain a better product and to be able to commercialize it into the markets. The consume of guinea pig meet is also growing due to its high nutritive values, low on fat and good taste, this is why the expectative from partners are focused on reaching a good level of production and also to inform about all the nutritional advantages from this animal´s meat. It is necessary to point out that the Association of women producers of guinea pigs in Cayambe (Aprocuy), is an organization that through the time that has been active has not developed a marketing plan, due to the lack of knowledge and support from the authorities of Cayambe. This is the reason why is needed to collaborate with the acquired knowledge through our college career. The following research document will help the association to take better decisions once it gets started since it will help as a tool to organize its internal structure and also to minimize the lack of experience. With this, the strategies and actions will be defined and this will allow to react and face a market that is becoming more competitive.